10 T generation by an epoxy impregnated GdBCO insert coil for the 25 T-cryogen-free superconducting magnet. (5th April 2016) - Awaji, Satoshi; Oguro, Hidetoshi; Watanabe, Kazuo; Hanai, Satoshi; Miyazaki, Hiroshi; Tosaka, Taizo; Ioka, Shigeru; Fujita, Shinji; Daibo, Masanori; Iijima, Yasuhiro
Abstract: A GdBa2 Cu3 O y (Gd123) insert coil for the 25 T cryogen-free superconducting magnet was constructed, installed and tested. We succeeded in the generation of 10 T using a Gd123 insert coil without a background field. The temperature of the Gd123 coil increased from 4.5 K gradually and reached about 5.5 K, when the magnet was energized with 0.036 A/s, which corresponds to a 1 hour energizing mode. The calculated and measured central magnetic fields are 10.61 T and 10.15 T, respectively, because of the magnetization current effect in RE123 tape. The maximum heat load by the AC-losses estimated from the temperature rise is about 3 W, which is consistent with the slab model combined with tape stacking effect.